PENGARUH STOCK SPLIT, DIVIDEN PER SHARE, DAN EARNING PER SHARE TERHADAP HARGA SAHAM: Studi Kasus Pada Perusahaan Perbankan BUMN Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2021 - Samudra Pandu Fortuna; Siti Mundiroh (Pusat Riset dan Inovasi Nasional, 2023)
This research is a quantitative research with a descriptive method, the data used is secondary data in the form of financial statements containing numbers then tested and describe or provide an overview of the results. This study aims to analyze and obtain empirical evidence of the effect of stock splits, dividends per share, and earnings per share on share prices in state-owned banking companies listed on the Indonesia Stock Exchange in 2014-2021. The population used in this study is state-owned banking companies listed on the Indonesia Stock Exchange in 2014-2021, totaling 4 companies. The selection of samples in this study used purposive sampling techniques, so that the number of companies was 4 with years of research for 8 years, the total research data obtained was 32. The data analysis technique used is panel data regression using the help of Eviews software version 9. The test results show that the variables stock split, dividend per share (dps), and earnings per share (eps) affect the stock price.